Modelling, and characterization of 3D printed cellular structures - Kucewicz, Michał; Baranowski, Paweł; Małachowski, Jerzy; Popławski, Arkadiusz; Płatek, Paweł (Materials & design, 2018)
•Three different cellular structures are fabricated by FDM of ABSplus material•Mechanical properties of the ABSplus material are determined•Mesh sensitivity study is performed to assess the influence of mesh type and mesh size•Crashworthiness properties of the three cellular structures are assessed during experimental and numerical testing [Display omitted] A procedure for characterizing the deformation process of a regular cellular structure under static loading conditions is presented. Three different topologies with similar relative densities were designed and fabricated by fused deposition modelling of ABSplus material. In the first stage, the material properties of the samples were evaluated and numerically correlated with experimental data. Experimental compression tests were performed on a universal strength machine. The comparison of the results of experiments and finite element analyses indicated acceptable similarity in terms of deformation, failure and force characteristics. Additionally, a mesh sensitivity study was performed, and the influence of the mesh on the obtained results was assessed. Finally, different types of elements for the discrete models of cellular structures were investigated. Two different approaches were considered for studying the energy-absorption properties of the cellular structures: with and without implementation of the erosion criterion for simulating material failure.